Oxygen radicals and nitric oxide in rat mesenteric ischaemia-reperfusion: Modulation by L-arginine and N-G-nitro-L-arginine methyl ester - YALÇIN, AHMET SUHA; DAĞLI, EMRULLAH TOLGA; HAKLAR, GONCAGÜL; YÜKSEL, MERAL (WILEY, 1998)
1. The aims of the present study were to detect changes in superoxide anion (O-2(.-)), nitric oxide (NO) and other reactive oxygen species (ROS) directly by measurement of chemiluminescence (CL) and to investigate the role of L-arginine, a nitric oxide synthase (NOS) substrate, and N-G-nitro-L-arginine methyl ester (L-NAME), a NOS inhibitor, together with their molecular enantiomers D-arginine and D-NAME, in a rat mesenteric ischaemia-reperfusion (I/R) model. 2, Seventy-nine female Wistar albino rats were divided into eight groups, The first three groups underwent sham operation; group 1 was the control group, group 2 received L-arginine and group 3 received L-NAME. Ischaemia was produced in the remaining five groups by ligation of the superior mesenteric artery for 30 min followed by 60 min reperfusion, Group 4 rats were control I/R rats and groups 5-8 received either L-arginine, L-NAME, D-arginine or D-NAME, respectively. 3, Both luminol and lucigenin CL was significantly increased in I/R groups compared with sham-operated groups. L-Arginine significantly reduced CL measurements. D-Arginine was also protective, but not as much as L-arginine. Both L- and D-arginine had in vitro O-2(.-)-scavenging potential, as tested by the xanthine-xanthine oxidase system. N-G-Nitro-L-arginine methyl ester decreased lipid peroxidation values in addition to reducing CL measurements. Nitric oxide concentrations were significantly increased in VR groups in comparison with sham-operated groups. Peroxynitrite formation was increased by I/R. Treatment with L-NAME was beneficial by reducing NO concentrations in the reperfused ileum, 4, In our I/R model, O-2(.-), NO and other ROS were increased. Although NOS inhibitors were effective in reducing oxidative damage, increasing NO concentrations with L-arginine was also beneficial, presumably due to the ability of L-arginine to inhibit phagocyte adherence and its radical scavenging potential. In fact, NO may have different effects in terms of tissue injury or protection depending on the concentration of oxygen and the haemodynamic state of the tissue.
Keywords: chemiluminescence; mesenteric ischaemia/reperfusion; nitric oxide; reactive oxygen species; superoxide radical; thiobarbituric acid-reactive substances; SUPEROXIDE; INJURY; PEROXYNITRITE